Pengaruh Model Kepemimpinan Transformasional Kepala Sekolah Terhadap Peningkatan Kompetensi Pedagogik Dalam Pengembangan Kurikulum Dan Pemanfaatan Teknologi Informasi Pada Guru Smk Negeri Se Kabupaten Demak - Suhadi, Suhadi; Kusrina, Tity; Suriswo , Suriswo (Jurnal Pendidikan Indonesia, 2025)
This study aims to analyze the influence of the transformational leadership model of school principals on improving pedagogic competence in curriculum development and the use of information technology in State Vocational School teachers throughout Demak Regency. Transformational leadership is a leadership approach that focuses on empowering and inspiring members to achieve common goals through positive change in the organization. This study uses a quantitative method with a survey research design. Data was collected through a questionnaire distributed to 100 State Vocational School teachers in Demak Regency, which was analyzed using a simple linear regression analysis technique. The results of the study show that the transformational leadership model of school principals has a positive and significant influence on improving teachers' pedagogic competence, especially in curriculum development and the use of information technology. These findings show the importance of the role of school principals in creating an environment that supports teacher professionalism, which in turn can improve the quality of learning in vocational schools. This research is expected to contribute to education policy, especially in the development of effective school leadership to improve the quality of teaching at the vocational level.